ANALISIS TINGKAT PENGETAHUAN DAN PERSEPSI SWAMEDIKASI OBAT ANALGETIK PADA SISWA DI SMAN 3 CIREBON - Nurrahma Berlian, Febia; Azrul Zuniarto, Ahmad; Pandanwangi, Siti; Rubihatlan, Encis; Minhatul Maula, Ajni; Farhan Alfawwaz, Azriel; Salafi, Akil; Sri Virgianti, Deby (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2023)
Self-medication is the selection and use of drugs by individuals or family members without doctor's instructions, to treat conditions that are recognized or self-diagnosed. Analgesics or what is often referred to as pain-blocking drugs without losing consciousness. This study aims to determine the level of students' knowledge about self-medication of analgesic drugs at SMAN 3 Cirebon, to determine students' perceptions of self-medication of analgesic drugs at SMAN 3 Cirebon, to determine the level of knowledge and perceptions of students towards self-medication of analgesic drugs based on student characteristics, and to determine the level of knowledge and students' perceptions of self-medication of analgesic drugs based on the indicators of the questions assessed. This research method is a quantitative research using a descriptive design. The sampling technique used purposive sampling technique. Data collection used an e-questionnaire (google form) which was given to 82 respondents who met the inclusion and exclusion criteria. The data analysis technique of this research uses descriptive analysis. The results of the research on the level of knowledge and students' perceptions about self-medication of analgesic drugs at SMAN 3 Cirebon found that the level of knowledge obtained an average value of 78.96% was included in the good category. Students' perceptions obtained an average score of 83.63% included in the very good category. Based on the characteristics of respondents who have good knowledge and very good perception, most are at the age of 16 years, female gender, parents work as private employees, pain experienced by respondents in the last 1 month, namely body/muscle pain, history of drug use, namely paracetamol and places get medicine namely Pharmacy. The level of students' knowledge about self-medication of analgesic drugs based on the indicators of questions that were assessed correctly, namely: 78.66% on the indicator of the level of safety and accuracy of drug use, 74.39% on the indicator of drug dosage, 93.9% on the indicator of drug use, 64, 63% on the indicator of how to use the drug 74.39% on the indicator of drug side effects, 89.02% on the indicator of how to store it, 97.56% on the indicator of drug expiry time, and 64.63% on the indicator of drug destruction.